Circulating Tumour Cells, Circulating Tumour DNA and Circulating MicroRNA in Metastatic Breast Carcinoma - What is the Role of Liquid Biopsy in Breast Cancer? - Polasik, Arkadius; Tzschaschel, Marie; Schochter, Fabienne; De Gregorio, Amelie; Friedl, Thomas W. P.; Rack, Brigitte; Hartkopf, Andreas; Fasching, Peter; Schneeweiss, Andreas; Mueller, Volkmar; Huober, Jens; Janni, Wolfgang; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Dissemination of tumour cells and the development of solid metastases occurs via blood vessels and lymphatics. Circulating tumour cells (CTCs) and circulating tumour DNA (ctDNA) can be detected in venous blood in patients with early and metastatic breast cancer, and their prognostic relevance has been demonstrated on numerous occasions. Repeated testing for CTCs and ctDNA, or regular so-called "liquid biopsy", can be performed easily at any stage during the course of disease. Additional molecular analysis allows definition of tumour characteristics and heterogeneity that may be associated with treatment resistance. This in turn makes personalised, targeted treatments possible that may achieve both improved overall survival and quality of life.
EVALuna2:36179